2005
DOI: 10.1002/pits.20063
|View full text |Cite
|
Sign up to set email alerts
|

Mental health services in schools: A qualitative analysis of challenges to implementation, operation, and sustainability

Abstract: Schools are increasingly recognized as a critical venue for the provision of comprehensive behavioral and mental health services for students. Unfortunately, difficulties associated with operating programs in schools often prevent evidence-based practices from being implemented and sustained as intended. In this study, the experiences of school and community providers who were funded through the Safe Schools/Healthy Students Initiative to implement mental health services in a large, urban school district were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 26 publications
3
36
0
Order By: Relevance
“…The culture of most schools generally favors academic-related outcomes above other areas of development (Adelman & Taylor, 1998; Massey et al, 2005). Despite its importance for children with autism, socialization often is not prioritized in many schools, and school leadership may not consider socialization as falling under their aegis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The culture of most schools generally favors academic-related outcomes above other areas of development (Adelman & Taylor, 1998; Massey et al, 2005). Despite its importance for children with autism, socialization often is not prioritized in many schools, and school leadership may not consider socialization as falling under their aegis.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of research in implementation of other evidence-based mental health interventions in school settings has examined barriers to implementation (Forman, Olin, Hoagwood, Crowe, & Saka, 2009; Forman et al, 2013; Langley, Nadeem, Kataoka, Stein, & Jaycox, 2010; Massey, Armstrong, Boroughs, Henson, & McCash, 2005). These studies have identified a number of important barriers to implementation, including staff’s competing priorities and responsibilities, the lack of administrator and teacher support, difficulty obtaining resources and materials, and finding time for the intervention in the school day (Forman et al, 2013; Langley et al, 2010; Massey et al, 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Qualitative methodology, and in particular the use of focus groups, is particularly effective for exploring feedback, perspectives, and knowledge of multiple stakeholders during program evaluation (Hydén & Bülow, 2003;Massey, 2011;Massey, Armstrong, Boroughs, Henson, & McCash, 2005). Accordingly, focus groups were conducted at the end of the school year with caregivers and teachers of children who were involved in the pilot project.…”
Section: Methodsmentioning
confidence: 99%
“…Massey, Armstrong, Boroughs, Henson, and McCash (2005) recommended that teachers receive ongoing training to increase understanding of the intervention process and how interventions function with the academic curriculum. This training also promotes intervention fidelity and consistency.…”
Section: Smhmentioning
confidence: 99%